A Stable Saddle‐Shaped Polycyclic Hydrocarbon with an Open‐Shell Singlet Ground State. Issue 12 (15th February 2017) - Ma, Ji; Liu, Junzhi; Baumgarten, Martin; Fu, Yubin; Tan, Yuan‐Zhi; Schellhammer, Karl Sebastian; Ortmann, Frank; Cuniberti, Gianaurelio; Komber, Hartmut; Berger, Reinhard; Müllen, Klaus; Feng, Xinliang
Abstract: Diindeno‐fused bischrysene, a new diindeno‐based polycyclic hydrocarbon (PH), was synthesized and characterized. It was elucidated in detailed experimental and theoretical studies that this cyclopenta‐fused PH possesses an open‐shell singlet biradical structure in the ground state and exhibits high stability under ambient conditions ( t 1/2 =39 days). The crystal structure unambiguously shows a novel saddle‐shaped π‐conjugated carbon skeleton due to the steric hindrance of the central cove‐edged bischrysene unit. UV/Vis spectral measurements revealed that the title molecule has a very narrow optical energy gap of 0.92 eV, which is consistent with the electrochemical analysis and further supported by density functional theory (DFT) calculations. Abstract : Stay in the saddle : A curved polycyclic hydrocarbon synthesized by extending the twisted bischrysene core by two indene units displayed a stable singlet biradical structure in the ground state. X‐ray crystallographic analysis clearly revealed its saddle‐shaped conformation.